Need Assessment Mubaligh Perempuan dalam Meningkatkan Pemahaman Keagamaan Masyarakat - Zakia, Rahima; Jusmawati, Jusmawati; Eliza, Eliza (Universitas Islam Negeri Imam Bonjol Padang, 2023)
This research is important because it sees the phenomenon that there are still many religious issues related to women's specific problems that have not been completely answered. Women's limited knowledge regarding women-specific issues leads to violations of Islamic teachings, both related to menstruation, junub, and household responsibilities. Balanced explanations and information regarding women's problems are often not obtained from male missionaries, and sometimes it even seems that there are subjective nuances that position women as objects of blame. The research was conducted using qualitative methods, research informants were congregations and active female preachers. Determining the informants using the next key informant using the snowball sampling technique. Data collection techniques use interviews, documentation studies and observation. This article explains that congregations need female missionaries to be able to discuss and share information regarding specific issues regarding women, the figure of a female missionary that the congregation wants includes having substantive competence and methodological competence. Female missionaries have quite high opportunities as evidenced by the community's enthusiastic acceptance of tabligh, while female missionaries face busy household duties, the place where tabligh is carried out is far from their domicile, and physical strength is not possible.